AB0824 Synovial Fluid Analysis in A Rheumatology Department. Past and Present. (15th July 2016) - Cuevas, P.; Rodriguez, S.; Inciarte, J.; Peris, P.; Monegal, A.; Guañabens, N.
Abstract : Background: For decades the Departments of Rheumatology have used synovial fluid analysis for the differential diagnosis of various arthropathies, especially microcrystalline diseases. However, it is possible that access to new diagnostic techniques and new treatments has changed the frequency and characteristics of synovial fluid analysis. Objectives: To compare the frequency and findings in synovial fluid analyses in two periods 10 years apart. Methods: Retrospective cross-sectional study evaluating the synovial fluid analysis reports from a Rheumatology Department (including outpatient, inpatient and emergency departments) carried out for a 4-year period (2012- 2015). The results were compared with those obtained in a previous study conducted between 1998–2005. Results: During the last 4 years we have analyzed a total of 440 samples of synovial fluid, with an average of 110±24.8 samples per year (range: 135–78), while in the previous study (1998–2005) 1, 881 synovial fluid samples were analyzed, with an average of 235±54.8 samples per year (range: 326–162), decreasing the number of fluid analysis evaluations by 53%. In 31.8% of the current samples and in 18.8% of samples of the previous study microcrystals were detected. The identification of monosodium urate crystals (MSU) were observed in 50% and 49.1% of the current vs. the previous analysis of the samples, respectively, whereas calcium pyrophosphate dihydrate crystals (CPPD) were present in 44.2% and 47.4%, respectively. The identification of both crystals in the same sample (UMS + CPPD) was reported in 6% and 1% of the analyses in the current and previous study, respectively. In both studies, MSU crystals were more frequent in males (83% vs. 89% in the current and previous study), whereas in women CPPD crystals were observed in 48% and 64% of current and previous analyses, respectively. Conclusions: In recent years a decrease in the number of synovial fluid analysis is observed. Although the proportion of synovial fluid analyses from pathologies other than crystal-induced arthritis has decreased, the proportion of detectable UMS and CPPD crystals has not changed. References: Frecuencia y tipo de microcristales en el análisis del líquido sinovial. Experiencia a largo plazo en un Servicio de Reumatología. M.A. Martínez, R. Reyes, C. Moll, F.J. Rodríguez, P. GόmezRoyo, P. Peris y N. Guañabens Hospital Clínic. Universidad de Barcelona. Reumatología Clinica. 2006;2 (Espec Congr):11–180. Disclosure of Interest: None declared